2001
DOI: 10.1530/eje.0.1440251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term administration of low-dose rhGH on IGF-I levels in obesity and Cushing's syndrome: indirect evaluation of sensitivity to GH

Abstract: Objective: To verify the hypothesis of an increased sensitivity to GH in obesity (OB) and Cushing's syndrome (CS). Design: We studied the effects of short-term administration of low-dose rhGH on circulating IGF-I levels in patients with simple OB or CS and in normal subjects (NS 2 ) underwent s.c. administration of 5 mg/kg per day rhGH at 2200 h for four days. Serum IGF-I, IGF-binding protein-3 (IGFBP-3), GHbinding protein (GHBP), insulin and glucose levels were determined at baseline and 12 h after the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
(32 reference statements)
1
33
0
1
Order By: Relevance
“…The levels were elevated in severely obese subjects (5,35) and this has been suggested to compensate for the low GH secretion (34). Others have found levels of GHBP to be similar in obese and lean subjects (36). IGFBP-1 levels are known to be inversely related to insulin levels and thus lower in obese subjects (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels were elevated in severely obese subjects (5,35) and this has been suggested to compensate for the low GH secretion (34). Others have found levels of GHBP to be similar in obese and lean subjects (36). IGFBP-1 levels are known to be inversely related to insulin levels and thus lower in obese subjects (37).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed tissue responsiveness to GH in morbid obesity. By using IGF-I generation tests, Maccario et al (36) found a more prominent response in obese women compared with lean women. Among the obese subjects, a subgroup with Cushing's disease had the most marked response, leading the authors to conclude that both hyperinsulinemia and hypercortisolism enhance sensitivity to GH.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results on GH secretion in obesity, our results suggest that the reduction in GH secretion is only partially translated into reduced IGF-I secretion. The reason for this is unclear, but again, an increase in GH sensitivity has been discussed (25). In a population-based study with 400 subjects, a negative correlation of IGF-I with BMI was found that disappeared after adjustment for age (26).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is characterized by blunted GH secretion (16,19) but reports of IGF-I levels in obese subjects are divergent. Some authors have reported decreased levels of IGF-I (20)(21)(22), while others have found normal levels (23)(24)(25), which could be due to an increased GH sensitivity in obese subjects (25). Negative correlations of IGF-I levels to visceral fat areas, assessed by computed tomography scan (23,26,27) have been reported even in the absence of significant correlations between body mass index (BMI) and IGF-I (23), suggesting that the amount of visceral fat is an important determinant of IGF-I levels.…”
Section: Introductionmentioning
confidence: 99%
“…Há evidên-cias de maior sensibilidade da ação do GH, tais como maior nível de GHBPs (e conseqüentemente de receptores de GH) e o achado de que administração de baixas doses de rhGH tem efeito estimulatório na produção de IGF1 maior em obesos do que em indivídu-os de peso normal (42). Além disso, a redução do peso após cirurgia bariátrica acarreta elevação marcante de parâmetros do perfil de secreção de 24 horas de GH (ritmo) em obesas grau III sem alteração do nível de ghrelina, sugerindo um papel limitado desta na regulação fisiológica do eixo somatotrófico (43).…”
Section: Eixo Somatotróficounclassified